(untitled) (The Conference Hub, 2025)
The requirements for learning and teaching English are changing every hour. Explaining the most important elements of language learning in a correct and easy way requires high pedagogical skills from the teacher. The most basic foundation of learning English is reading skills. This article extensively discusses models for improving reading skills.